Manufacturing technology, lean and strategic flexibility the silver bullet for Malaysia lean manufacturers - Mohamed Ismail, Risyawati; Che Razak, Razli; Mad Lazim, Halim (Penerbit UTM Press, 2015)
The purpose of this paper is to conceptually propose the elements that constitute an ideal manufacturing strategy framework needed by Malaysian manufacturing sector.Malaysian manufacturing sector has so far underwent various challenges and exhibited fluctuating performance as reaction to these challenges.This paper is the product of an extensive literature review done on previous researches on the subject of manufacturing strategy and performance.In this review, the subject matter was comprehensively studied, and thoroughly discussed from the strategic perspective of Malaysian manufacturing sector.This paper manages to provide a fundamental framework, for expert in the area of manufacturing strategy and performance, emphasizing on the complementary effect of multiple strategies on performance.The subject approach is relatively new in Malaysia, however based on previous studies and the critical impact of manufacturing towards the economic health of Malaysia, the sector is in dire need of suitable and favorable manufacturing strategy in order to continue to compete globally. Malaysian manufacturing sector is still lacking of a strategic approach on its national manufacturing direction and guideline, to serve as the launching pad for the sector's sustainable growth.This paper not only ventures into a new perspective of strategy-performance research, but it also explores the possibility of studying different complementing strategies impact on the performance of manufacturers.